2019
DOI: 10.1016/j.ijhydene.2019.02.217
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic emission-based damage characterization of 70 MPa type IV hydrogen composite pressure vessels during hydraulic tests

Abstract: This paper aims to apply an acoustic emission (AE) method to characterize the damage mechanisms of composite hydrogen pressure vessels (Type IV) with a service pressure of 70 MPa. First, AE signals were captured during the multi-step loading of two vessels.Second, AE feature parameters in time-domain and frequency-domain analyses such as amplitude, frequency, and energy were studied. A multi-parameter statistical analysis (MPSA) method based on empirical mode decomposition (EMD) and K-means algorithm was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The fibers were used to measure strains in several thicknesses of the composite layup and could also be used to detect damage after impact by analyzing the backscattered light. Liao et al 11 used acoustic emission to recognize failure during hydraulic testing. A relation was found between the emitted sound and the corresponding failure event.…”
Section: Introductionmentioning
confidence: 99%
“…The fibers were used to measure strains in several thicknesses of the composite layup and could also be used to detect damage after impact by analyzing the backscattered light. Liao et al 11 used acoustic emission to recognize failure during hydraulic testing. A relation was found between the emitted sound and the corresponding failure event.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the damage detection of composite shell is very important for the safety of CHPHSV. 40 The damage detection methods are summarized in Table 7. In Table 7, the FF denotes fiber failure.…”
Section: Damage Detection Of Composite Shell Of Chphsvmentioning
confidence: 99%
“…Three different failure modes, that is, matrix cracking, fiber matrix interface debonding, and fiber breakage, were identified by the multi-parameter statistical analysis method with the amplitude, energy, and absolute energy of the obtained sound pressure signal. 40 H. Y. Chou et al found that the uncertainty of failure life of composite shell under cyclic loading was related to the randomness of carbon fiber breakage. 55 However, the AE method cannot determine the damage area.…”
Section: Damage Detection Of Composite Shell Of Chphsvmentioning
confidence: 99%
See 1 more Smart Citation
“…The acoustic emission (AE) technique is now recognized as an important SHM technique and has been used in damage monitoring and evaluation of various engineering structures. 3,14,20,27 The most distinct advantage of the AE technique over traditional NDT methods is that it can realize online monitoring, accurate detection and localization of the damage such as cracks inside the material based on the change in multiple AE characteristic parameters. 8 For exploiting the advantage of AE, numerous studies have been performed to identify crack initiation and characterize the fatigue crack growth phenomenon of various metallic materials and structures.…”
Section: Introductionmentioning
confidence: 99%